2017
DOI: 10.1038/s41598-017-03029-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of genotype on endocrinal complications of Children with Alpha-thalassemia in China

Abstract: Alpha-thalassemia occurs with high frenquency in China. Four common α-globin gene deletion mutations (–SEA, -α3.7, and -α4.2, Haemoglobin Constant Spring (CS) mutation) were identified in Chinese patients. Individuals with alpha-thalassemia syndrome are more often of children. However report on endocrinal complications in children with alpha thalassemia in China are still absent. The present study aimed to investigate the impact of genotype on endocrinal complications in Chinese children. Association analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…A study involving 57 transfusion-dependent β-TM patients from Sun Yat-sen Memorial Hospital showed that 7% with β-TM was diagnosed with DM, and 24% had impaired fasting glucose 15. A study of 200 children with alpha-thalassemia discovered that DM was identified in 14 patients and 71.4% of them were 6 years old with no significant difference identified between males and females 16. In our previous study of adolescent, TM patients we found that the overall prevalence of diabetes and IFG in thalassaemic children under 18 years was 2% and 30%, respectively 8…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 57 transfusion-dependent β-TM patients from Sun Yat-sen Memorial Hospital showed that 7% with β-TM was diagnosed with DM, and 24% had impaired fasting glucose 15. A study of 200 children with alpha-thalassemia discovered that DM was identified in 14 patients and 71.4% of them were 6 years old with no significant difference identified between males and females 16. In our previous study of adolescent, TM patients we found that the overall prevalence of diabetes and IFG in thalassaemic children under 18 years was 2% and 30%, respectively 8…”
Section: Discussionmentioning
confidence: 99%
“…Growth failure in thalassemia may be attributed to economic status 24 and clinical factors such as the degree of chronic hypoxia, iron overload, several micronutrient deficiencies, and parental height. 25 , 26 In this study, the prevalence of growth failure was 15%, consistent with other studies (13%–21%), 10 , 12 with the failure more pronounced among our patients with NDHbH.…”
Section: Discussionmentioning
confidence: 99%
“…23 Health education, food fortification policies, and early detection monitoring are necessary to mitigate the risk of vitamin D deficiency and promote bone health and growth in thalassemia patients. 21 Growth failure in thalassemia may be attributed to economic status 24 and clinical factors such as the degree of chronic hypoxia, iron overload, several micronutrient deficiencies, and parental height. 25,26 In this study, the prevalence of growth failure was 15%, consistent with other studies (13%-21%), 10,12 with the failure more pronounced among our patients with NDHbH.…”
mentioning
confidence: 99%
“…Most complications are caused by increased iron sedimentation in tissues like heart, endocrine glands and these results in heart failure, arrhythmia, hypothyroidism, diabetes mellitus and so on. 2,3 A study has reported that 29.4% children with thalassemia had diabetes, 11.8% had hypothyroidism. 4 A local study by Ibrahim et al, 5 reported 13.8% hypothyroidism and 5.6% diabetes in children with thalassemia.…”
Section: Introductionmentioning
confidence: 99%